Implementation of Non-Communicable Disesase Risk Factors Surveillance in Posbindu Surabaya based on Surveillance Attribute (Study in Surabaya) - Elyda Rahmayanti; Arief Hargono (Universitas Airlangga, 2017)
ABSTRACT Non-communicable diseases (NCD) became causes of death in the world. Proportion of deaths due to NCD also NCD risk factors was increasing in Indonesia so, NCD control was required. NCD risk factors surveillance in Posbindu based on surveillance attribute at Surabaya was not optimal. Puskesmas have not established ≥20 Posbindu in each work area make NCD risk factors has not been identified. It may affect the resulting information representation to make the fundamental of policy control. The purpose of this research was to evaluate NCD risk factors surveillance system in Posbindu based on surveillance attribute in Surabaya. This research was a descriptive evaluative. The research subjects were NCD risk factors surveillance system with 16 program respondents and 77 Posbindu volunteers. Data collection were conducted with questionnaires and document studies. The results show that the system was simple, acceptable, has high sensitivity and stability, timely, and high quality data. While the assessment of flexibility and positive predictive value could not be done. The conclusion of this research was surveillance attribute was good but there were problems in surveillance system. The problem solving suggestion were community empowerment to purchase their own tools by the Posbindu volunteers, expert or laboratory confirmation record on the result of examination, and maintanace server of NCD website page. Keywords: surveillance attribute, NCD risk factors, Posbindu, surveillance